Cross-Linguistic Influence: Analyzing English Loanwords in Contemporary French (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study examines the lexical, grammatical, and stylistic adaptation of English loanwords in contemporary French, revealing their pervasive presence across various domains of French media and literature. Through quantitative and qualitative analyses, it investigates how these loanwords are integrated into the French linguistic framework, considering factors such as lexical gaps, grammatical conformity, and stylistic functions. The findings underscore the dynamic interplay between English and French, reflecting broader trends of globalization and cultural exchange in language usage.